EP1161 Exome analysis of vulvar and vaginal tumors reveals an antigen processing and presentation deficiency. (1st November 2019) - Bengrine, L; Fumet, JD; Favier, L; Richard, C; Arnould, L; Boidot, R
Abstract : Introduction/Background: The rare vaginal and vulvar cancers are considered to be histologically similar to cervical squamous cell carcinoma. However, mutational landscape differences between them are unclear. In the time of precision medicine and immunotherapy, a personalized therapy approach based on a detailed biological characterization of each tumor entity should be considered. This study aimed to identify differences and specific genetic alterations in vaginal and vulvar compared to cervical squamous cell carcinoma. Methodology: Using next generation sequencing (NGS), both somatic and germline exome sequencing of vulvar (n=11), vaginal (n=') and cervical cancer (n=11) were analyzed. To determine a potential sensitivity to immunotherapy, we studied tumor mutation burden, ratio indels, TCR clonality, neopeptides, Alexandrov's signatures, and copy number variation. Additionally a signaling pathway analysis was performed applying 2 different approaches (NCI and KEGG). Results: No significant differences were seen in the respective immunologic predictive biomarkers comparing the three tumor entities. The signaling pathway analysis revealed an alteration of antigen processing and presentation pathways in vulvar and vaginal cancer compared to cervical cancer (77 genes). Moreover, an activation of Notch signaling was found in vulvar and vaginal tumors. Vulvar and vaginal cancer reveal a comparable mutational landscape in the analyzed genes. Conclusion: NGS determines a potential immune evasion strategy of vulvar and vaginal tumors related to an alteration of antigen presentation. Our findings suggest that immunotherapy might be less efficient compared to cervical cancer. Targeting Notch and mTOR pathway may be a promising therapy approach in these rare tumors. Disclosure: Nothing to disclose